int foo(int N) {

if (N == 0)

return 1;

else

return N * foo(N-1);

}

int bar(int N) {

if (N == 1)

return 1;

for (int i = 1; i < N; i++){

bar(N-1);

}

}

int bazo(int N) {

if (N < 1)

return 1;

for (int i = 1; i < N*N; i++){

for (j = 1; j < i; j++) {

bazo(N/2);

}

}

}

int hard(int N) {

if (N < 1)

return 1;

return (N*hard(N/2))/hard(N-1);

}

Any computer science student shoud be able to calculate hat:

foo(N) = T(N) = T(N-1) = T(N)

bar(N) = T(N) = (N-1)*T(N-1)

bazo(N) = T(N) = N2*O(N2)*T(N/2)

hard(N) = T(N) = T(N/2)+T(N-1)

## No comments:

Post a Comment